2006
DOI: 10.1039/b606215f
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of energy transfer in perylene-cored anthracene dendrimers

Abstract: Quantitative evaluation of Förster-type fluorescence resonance energy transfer (FRET) was undertaken by statistical investigations on perylene-cored anthracene dendrimers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 14 publications
0
21
0
Order By: Relevance
“…Perylene and its analogues [1] are an interesting class of polyaromatic hydrocarbons (PAH) that are investigated for diverse applications including organic solar cells [2], fluorescence labeling [3], molecular sensors [4], and molecular electronics [5]. Perylene diimides have been the most studied perylene derivatives [67] because of the electron accepting properties of the π-system, which results from the electron withdrawing carbonyl substituents [8].…”
Section: Introductionmentioning
confidence: 99%
“…Perylene and its analogues [1] are an interesting class of polyaromatic hydrocarbons (PAH) that are investigated for diverse applications including organic solar cells [2], fluorescence labeling [3], molecular sensors [4], and molecular electronics [5]. Perylene diimides have been the most studied perylene derivatives [67] because of the electron accepting properties of the π-system, which results from the electron withdrawing carbonyl substituents [8].…”
Section: Introductionmentioning
confidence: 99%
“…[24] One of the most active areas of research involving PDI systems is related to their utilization in photoinduced electron-and/or energy-transfer processes. In this regard, electroactive units such as fluorenone and anthraquinone, [25] tetrathiafulvalene, [26] pyrene, [27] oligothiophene, [28] zinc phthalocyanine, [29] 3,4-ethylenedioxythiophene, [30] zinc porphyrin, [31] hexaazatriphenylenes, [32] anthracene dendrimers, [33] perylenemonoimide, [34] tetraboron-dipyrrin, [35] and poly(fluorene-alt-phenylene) [36] were connected to the PDI dye to reach molecular ensembles in which an electron-and/or energy-transfer event occurs. In the search for such electronic interaction involving PDI, supramolecular architectures were also recently described involving an oligo(p-phenylenevinylene), [37] a Abstract in French: De nouveaux assemblages covalents fullerne C 60 -pØrylne-3,4:9,10-bis(dicarboximide) (C 60 -PDI) (1-4) ont ØtØ synthØtisØs et caractØrisØs.…”
Section: Introductionmentioning
confidence: 99%
“…1), which exhibited light-harvesting functionalities from peripheral anthracene groups to the perylene cores. 5,6 During the course of our studies we found that energy transfer efficiencies were unaffected by relative orientation of the donor and acceptor chromophores within the dendrimer domains. In the present publication, we describe the results of continuing investigations, which delineate the mechanism of energy transfer in the multichromophore systems.…”
Section: Introductionmentioning
confidence: 73%